A biochar-based alkali-excited barrier control material and its preparation method and application
By using biochar and activated magnesium oxide co-ball milling in alkali excitation control materials, the composite alkali excitation agent is obtained, combined with in situ soil and ash body materials, the problems of long molding time and poor anti-seepage performance of existing materials are solved, and the effects of rapid molding and efficient anti-seepage are achieved.
Patent Information
- Application Number
- CN202411256078.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing alkali-excited barrier materials have long forming time and poor anti-seepage performance in rapid barrier scenarios, and have high alkalinity dependence and poor environmental friendliness, making it difficult to meet the needs of rapid molding and efficient anti-seepage.
Using biochar base-excitation barrier materials, a composite alkali excitation agent is prepared by co-ball grinding of activated magnesium oxide and biochar, and combined with in situ soil and ash material to form a barrier material with high efficiency and anti-seepage properties.
It has achieved rapid forming, the initial settling time is shortened by about 20 minutes, the compressive strength can reach 9.33MPa after 7 days, and the anti-seepage performance is significantly improved. The permeability coefficient meets the anti-seepage requirements, and is suitable for rapid obstacle control of emergency polluted sites.
Smart Images

Figure CN119118609B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an alkali-excited barrier control material, in particular to a biochar-based alkali-excited barrier control material, and also to a preparation method and application of the biochar-based alkali-excited barrier control material. Background Art
[0002] The current stage of accelerated industrialization and urbanization has brought about frequent environmental emergencies and environmental risks, and the environmental safety situation faces serious challenges. Sudden pollution often has the characteristics of high instantaneous concentration, difficulty in control, and complex composition. Pollutants will spread in a short period of time, causing great harm to the environment and human health. Therefore, it is very necessary to quickly block and control sudden pollution and cut off the source of infection.
[0003] In order to avoid the seepage and diffusion of pollutants, the barrier control material must be formed within a certain period of time and have good anti-seepage performance. Traditional cement barrier walls are widely used in the remediation of contaminated sites, but due to their slow hydration process, serious energy consumption in the production process, and poor anti-seepage performance, they are not suitable for rapid barrier control scenarios. Bentonite, solid waste cementitious materials, etc. perform well in terms of anti-seepage. Although they are low-cost and relatively green in production, they are also slow to form under normal circumstances.
[0004] At present, NaOH, Na2SiO3 and their mixtures in different proportions are commonly used as alkali activators. However, due to their high dependence on alkalinity and poor environmental friendliness, the material performance development is unstable. At the same time, the use process requires the calculation of water volume according to the modulus, and the effect is greatly affected by the alkali equivalent, which limits large-scale application. At the same time, under the demand for biochar's pollution interception performance, liquid activators cannot achieve uniform distribution of biochar. Therefore, it is very necessary to develop an alkali-activated barrier control material that is environmentally friendly, has stable development, and can meet the needs of introducing biochar and is suitable for rapid barrier control scenarios. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a biochar-based alkali-excited barrier control material, and also to provide a preparation method and application of the above-mentioned biochar-based alkali-excited barrier control material.
[0006] Technical solution: A biochar-based alkali-activated barrier control material of the present invention comprises 50-70% by mass of in-situ soil and 30-50% by mass of a colloidal material; wherein the colloidal material comprises 90-80% by mass of a ash material and 10-20% by mass of a composite alkali activator, wherein the composite alkali activator is obtained by co-ball milling of activated magnesium oxide and biochar, wherein the mass ratio of biochar to magnesium oxide is 0.5-6:100; and the water-solid mass ratio is 22-28%.
[0007] Among them, the mass ratio of biochar to magnesium oxide is preferably 1 to 4:100.
[0008] The ash material is one or a combination of blast furnace slag, fly ash, coal gangue, steel slag, etc.; preferably, blast furnace slag and fly ash are combined in a mass ratio of 1:1.
[0009] The preparation method of the composite alkali activator is as follows: screening the biochar raw materials and crushing them, pyrolyzing them at 500-700°C for 1-3h to obtain the biochar and grinding and sieving them; drying the activated magnesium oxide and the biochar at 60-70°C for 4-6h to obtain a dry mixture; grinding the dry mixture in a ball mill for 2-3h to obtain the composite alkali activator.
[0010] Wherein, the rotation speed of the ball mill is 100-300r / min, and the ball-to-material ratio is 4:1-8:1.
[0011] Wherein, the particle size of the sand is ≤630 μm, the activity of the magnesium oxide is 55-70%, and the particle size of the biochar is ≤50 μm.
[0012] The method for preparing the above-mentioned biochar-based alkali-excited barrier control material comprises the following steps:
[0013] (1) preparing ash material and composite alkali activator according to mass percentage, and uniformly stirring and mixing for 3-5 minutes to obtain a premix;
[0014] (2) Take 60-70% of the premix prepared in step (1), add water to the premix at a water-to-solid mass ratio of 22-28%, stir at a low speed for 4-5 minutes to form a muddy slurry, then add in-situ soil at a clay-rubber ratio of 3:7-5:5, stir rapidly for 2-3 minutes, and finally add the remaining premix and stir rapidly for 2-3 minutes to obtain a biochar-based alkali-activated barrier control material.
[0015] Wherein, the curing conditions of the preparation method are 25±2°C and humidity ≥75%.
[0016] Wherein, in step (2), the low-speed stirring has a rotation speed of 700-900 r / min; and the high-speed stirring has a rotation speed of 1500-1800 r / min.
[0017] The above-mentioned biochar-based alkali-activated barrier control material can also be used in the rapid barrier control of emergency contaminated sites and soil pollution control or remediation.
[0018] The application includes the following steps: excavating a trench at the proposed barrier location by using a trenching machine; configuring biochar-based alkali-activated barrier control materials, and after sufficient mixing, pumping the mud made from the biochar-based alkali-activated barrier control materials back into the trench; after pouring, covering the top of the barrier control material with a layer of in-situ soil to prevent the top from shrinking and cracking.
[0019] Principle of the invention: The biochar-based alkali-activated barrier control material of the present invention selects active magnesium oxide as the alkali source. Compared with the traditional hydroxide-activated slag, it has lower alkalinity and higher environmental friendliness; powdered active magnesium oxide is more conducive to the introduction of biochar and makes it evenly dispersed; solid waste-based components replace conventional cement-based materials with blast furnace slag or fly ash, etc., accounting for 30-50% of the material system, which improves the waste utilization rate and is beneficial to saving resources and environmental protection; and biochar is further doped in the composite alkali activator, which not only improves the activity of magnesium oxide to promote the activation effect, but also improves the disadvantage of slow hydration rate caused by low alkalinity. Among them, the improvement effect is most obvious when 2% by mass of corn straw biochar is added.
[0020] The composite alkali activator in the above raw materials is a hydrotalcite generated by the reaction of active magnesium oxide and slag, which can better fill the gaps in the hydration products; biochar can also play a role in filling the gaps, further improving the anti-seepage effect, and the permeability coefficient meets the anti-seepage requirements (10 -9 m / s). Moreover, activated magnesium oxide and biochar achieve a synergistic effect. Biochar promotes the hydration rate. The alkaline environment provided by magnesium oxide can also modify biochar in conjunction with the ball milling process, promoting the formation of its porous structure and forming a good interception effect on pollutants. It is very suitable for application in emergency control scenarios. In the preparation method, dry mixing is first performed and then mixed in batches, so as to achieve the sufficiency and uniformity of the mixing of various raw materials, so that the performance of the material is further improved.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0022] (1) The biochar-based alkali-activated barrier control material of the present invention has readily available raw materials, low cost, low carbon emissions, and high economic benefits; it is easy to use and does not require the preparation of the alkali equivalent and water glass modulus of traditional alkali-activated materials, and is relatively easy to use;
[0023] (2) It can be quickly formed in the rapid control of emergency contaminated sites, and the initial setting time can be as short as 34 minutes, which is about 20 minutes shorter than that of unmodified materials. Compared with traditional alkali-activated materials, the early strength is improved. Under the standard curing condition of 7 days, its compressive strength can reach 9.33MPa, and it is suitable for low mortar-sand ratio conditions, with good engineering application prospects;
[0024] (3) The biochar-based alkali-activated barrier control material of the present invention can better introduce biochar and magnesium oxide for synergistic enhancement through ball milling, and the anti-seepage effect is improved compared with traditional cement walls and unmodified materials. At the same time, it has better chemical compatibility and can meet the anti-seepage requirements and achieve barrier effect under the action of pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1The activity changes of the composite base activators prepared in Examples 1-4 measured by the hydration method;
[0026] Figure 2 The changes in the unconfined compressive strength of the biochar-based alkali-stimulated barrier control materials at 0.5d and 1d with different mortar-sand ratios obtained in Example 2 and Examples 5-6;
[0027] Figure 3 The unconfined compressive strength of the resistance control materials described in Examples 1-4 and Comparative Examples 1-5 varies with curing time;
[0028] Figure 4 These are the barrier performance test results of the barrier materials described in Examples 1-4 and Comparative Examples 6-8. DETAILED DESCRIPTION
[0029] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.
[0030] Example 1
[0031] The biochar-based alkali-activated barrier control material of the present invention comprises 70% by mass of in-situ soil and 30% by mass of a colloidal material; wherein the colloidal material comprises 85% by mass of a ash material and 15% by mass of a composite alkali activator, wherein the composite alkali activator is obtained by co-ball milling of activated magnesium oxide and biochar, wherein the mass ratio of biochar to magnesium oxide is 1:100; and the water-solid mass ratio is 24%.
[0032] The preparation method of the composite alkali activator is as follows: screen the biochar raw materials and crush them, pyrolyze them in a tubular furnace at 500-700°C for 2 hours to obtain biochar, and grind and sieve them; dry the activated magnesium oxide and biochar at 60°C for 5 hours to obtain a dry mixture; put the dry mixture into an agate jar, put it into a planetary ball mill and grind it for 3 hours at a speed of 210r / min and a ball-to-material ratio of 5:1 to obtain a magnesium oxide@biochar composite alkali activator.
[0033] The above-mentioned biochar-based alkali-activated barrier control material is prepared by:
[0034] (1) Raw material mixing: 42.5% slag, 42.5% fly ash, and 15% composite alkali activator are mixed in a concrete mixer and uniformly mixed for 5 minutes to obtain a premix;
[0035] (2) 60% of the premix is put into a concrete mixer, water is added to the dry mix according to a water-to-solid mass ratio of 24%, and stirred at a low speed for 5 minutes to form a muddy slurry, and then the in-situ soil is added according to a clay-soil ratio of 3:7, and stirred rapidly for 3 minutes. Finally, the remaining 40% of the premix is added and stirred rapidly for 2 minutes to obtain a biochar-based alkali-activated barrier control material, recorded as MgO@1BC.
[0036] Example 2
[0037] The biochar-based alkali-activated barrier control material of the present invention, compared with Example 1, changes the mass ratio of biochar to magnesium oxide: it comprises 70% by mass of in-situ soil and 30% by mass of colloidal material; wherein the colloidal material comprises 85% by mass of ash material and 15% by mass of a composite alkali activator, wherein the composite alkali activator is obtained by co-ball milling of activated magnesium oxide and biochar, and the mass ratio of biochar to magnesium oxide is 2:100; and the water-solid mass ratio is 24%.
[0038] The preparation method of the composite alkali activator is as follows: screen the biochar raw materials and crush them, pyrolyze them in a tubular furnace at 500-700°C for 2 hours to obtain biochar, and grind and sieve them; dry the activated magnesium oxide and biochar at 60°C for 5 hours to obtain a dry mixture; put the dry mixture into an agate jar, put it into a planetary ball mill and grind it for 3 hours at a speed of 210r / min and a ball-to-material ratio of 5:1 to obtain a magnesium oxide@biochar composite alkali activator.
[0039] The above-mentioned biochar-based alkali-activated barrier control material is prepared by:
[0040] (1) Raw material mixing: 42.5% slag, 42.5% fly ash, and 15% composite alkali activator are mixed in a concrete mixer and uniformly mixed for 5 minutes to obtain a premix;
[0041] (2) 60% of the premix is put into a concrete mixer, water is added to the dry mix according to a water-to-solid mass ratio of 24%, and stirred at a low speed for 5 minutes to form a muddy slurry, and then the in-situ soil is added according to a clay-soil ratio of 3:7, and stirred rapidly for 3 minutes. Finally, the remaining 40% of the premix is added and stirred rapidly for 2 minutes to obtain a biochar-based alkali-activated barrier control material, recorded as MgO@2BC.
[0042] Example 3
[0043] The biochar-based alkali-activated barrier control material of the present invention, compared with Example 1, changes the mass ratio of biochar to magnesium oxide: it comprises 70% by mass of in-situ soil and 30% by mass of colloidal material; wherein the colloidal material comprises 85% by mass of ash material and 15% by mass of a composite alkali activator, wherein the composite alkali activator is obtained by co-ball milling of activated magnesium oxide and biochar, and the mass ratio of biochar to magnesium oxide is 3:100; and the water-solid mass ratio is 24%.
[0044] The preparation method of the composite alkali activator is as follows: screen the biochar raw materials and crush them, pyrolyze them in a tubular furnace at 500-700°C for 2 hours to obtain biochar, and grind and sieve them; dry the activated magnesium oxide and biochar at 60°C for 5 hours to obtain a dry mixture; put the dry mixture into an agate jar, put it into a planetary ball mill and grind it for 3 hours at a speed of 210r / min and a ball-to-material ratio of 5:1 to obtain a magnesium oxide@biochar composite alkali activator.
[0045] The above-mentioned biochar-based alkali-activated barrier control material is prepared by:
[0046] (1) Raw material mixing: 42.5% slag, 42.5% fly ash, and 15% composite alkali activator are mixed in a concrete mixer and uniformly mixed for 5 minutes to obtain a premix;
[0047] (2) 60% of the premix is put into a concrete mixer, water is added to the dry mix according to a water-to-solid mass ratio of 24%, and stirred at a low speed for 5 minutes to form a muddy slurry, and then the in-situ soil is added according to a clay-soil ratio of 3:7, and stirred rapidly for 3 minutes. Finally, the remaining 40% of the premix is added and stirred rapidly for 2 minutes to obtain a biochar-based alkali-activated barrier control material, recorded as MgO@3BC.
[0048] Example 4
[0049] The biochar-based alkali-activated barrier control material of the present invention, compared with Example 1, changes the mass ratio of biochar to magnesium oxide: it comprises 70% by mass of in-situ soil and 30% by mass of colloidal material; wherein the colloidal material comprises 85% by mass of ash material and 15% by mass of a composite alkali activator, wherein the composite alkali activator is obtained by co-ball milling of activated magnesium oxide and biochar, and the mass ratio of biochar to magnesium oxide is 4:100; and the water-solid mass ratio is 24%.
[0050] The preparation method of the composite alkali activator is as follows: screen the biochar raw materials and crush them, pyrolyze them in a tubular furnace at 500-700°C for 2 hours to obtain biochar, and grind and sieve them; dry the activated magnesium oxide and biochar at 60°C for 5 hours to obtain a dry mixture; put the dry mixture into an agate jar, put it into a planetary ball mill and grind it for 3 hours at a speed of 210r / min and a ball-to-material ratio of 5:1 to obtain a magnesium oxide@biochar composite alkali activator.
[0051] The above-mentioned biochar-based alkali-activated barrier control material is prepared by:
[0052] (1) Raw material mixing: 42.5% slag, 42.5% fly ash, and 15% composite alkali activator are mixed in a concrete mixer and uniformly mixed for 5 minutes to obtain a premix;
[0053] (2) 60% of the premix is put into a concrete mixer, water is added to the dry mix according to a water-to-solid mass ratio of 24%, and stirred at a low speed for 5 minutes to form a muddy slurry, and then the in-situ soil is added according to a clay-soil ratio of 3:7, and stirred rapidly for 3 minutes. Finally, the remaining 40% of the premix is added and stirred rapidly for 2 minutes to obtain a biochar-based alkali-activated barrier control material, recorded as MgO@4BC.
[0054] Example 5
[0055] The biochar-based alkali-activated barrier control material of the present invention, compared with Example 2, changes the colloid-soil ratio: it comprises 40% by mass of in-situ soil and 60% by mass of colloid material; wherein the colloid material comprises 85% by mass of ash material and 15% by mass of a composite alkali activator, wherein the composite alkali activator is obtained by co-ball milling of activated magnesium oxide and biochar, and the mass ratio of biochar to magnesium oxide is 2:100; the water-solid mass ratio is 24%.
[0056] Example 6
[0057] The biochar-based alkali-activated barrier control material of the present invention, compared with Example 2, changes the colloid-soil ratio: it comprises 50% by mass of in-situ soil and 50% by mass of colloid material; wherein the colloid material comprises 85% by mass of ash material and 15% by mass of a composite alkali activator, wherein the composite alkali activator is obtained by co-ball milling of activated magnesium oxide and biochar, and the mass ratio of biochar to magnesium oxide is 2:100; the water-solid mass ratio is 24%.
[0058] Comparative Example 1
[0059] An alkali-activated barrier control material is disclosed. Compared with Example 1, the composite alkali activator is replaced by an equal amount of common activated magnesium oxide, and the rest of the preparation methods are the same. The product is recorded as MgO.
[0060] Comparative Example 2
[0061] An alkali-activated barrier control material. Compared with Example 1, biochar and activated magnesium oxide are only mixed without ball milling; the rest of the preparation methods are the same, and the obtained product is recorded as MgO+1BC.
[0062] Comparative Example 3
[0063] An alkali-activated barrier control material. Compared with Example 2, the biochar and activated magnesium oxide are only mixed without ball milling; the rest of the preparation methods are the same, and the obtained product is recorded as MgO+2BC.
[0064] Comparative Example 4
[0065] An alkali-activated barrier control material. Compared with Example 3, the biochar and the activated magnesium oxide are only mixed without ball milling; the rest of the preparation methods are the same, and the obtained product is recorded as MgO+3BC.
[0066] Comparative Example 5
[0067] An alkali-activated barrier control material. Compared with Example 4, biochar and activated magnesium oxide are only mixed without ball milling; the rest of the preparation methods are the same, and the obtained product is recorded as MgO+4BC.
[0068] Comparative Example 6
[0069] A base-activated barrier control material is disclosed. Compared with Example 1, the composite base activator is replaced by an equal amount of ball-milled active magnesium oxide. The rest of the preparation method is the same, and the product is recorded as MgO*.
[0070] Comparative Example 7
[0071] A traditional cement barrier wall material. Compared with Example 1, the colloidal material of the material is replaced by ordinary silicate cement, that is, cement: in-situ soil = 3:7, and the rest of the preparation method is consistent with Example 1.
[0072] Comparative Example 8
[0073] A base-activated barrier control material. Compared with Example 1, the base activator is replaced by sodium hydroxide, and the solution is prepared to have a pH close to that of Example 1 and is added according to the water-to-solid ratio. The rest of the preparation method is the same, and the product is recorded as NaOH.
[0074] The performance tests were carried out on the materials obtained in the above embodiments and comparative examples:
[0075] Referring to the "Highway Geotechnical Test Code" (JTG 3430-2020) and ASTM D4972, the performance of the resistance control material was tested. The basic physical properties are shown in Tables 1 and 2:
[0076] Table 1. Performance of the resistance control materials of Examples 1 to 4 and Comparative Examples 1 to 8
[0077]
[0078]
[0079] Table 2 Unconfined compressive strength (MPa) of the resistance control materials of Examples 1 to 4 and Comparative Examples 1 to 8
[0080] Sample serial number 0.5d 1d 3d 7d Example 1 MgO@1BC 0.47 1.15 3.31 7.03 Example 2 MgO@2BC 0.55 1.29 2.65 9.33 Example 3 MgO@3BC 0.58 1.10 3.95 8.96 Example 4 MgO@4BC 0.46 1.00 3.27 7.90 Comparative Example 1 MgO 0.20 0.36 0.53 1.76 Comparative Example 2 MgO+1BC 0.17 0.41 0.50 1.69 Comparative Example 3 MgO+2BC 0.19 0.31 0.39 1.91 Comparative Example 4 MgO+3BC 0.15 0.35 0.67 1.85 Comparative Example 5 MgO+4BC 0.20 0.39 0.50 1.68 Comparative Example 6 MgO* 0.35 0.66 1.52 2.95 Comparative Example 8 NaOH 0.51 0.94 1.86 6.02
[0081] From Tables 1 to 2 and Figures 2-3It can be seen that the barrier control material excited by the composite alkali activator prepared by ball milling the activated magnesium oxide and biochar proposed in the present invention has the characteristics of high early strength, shorter initial setting time, better construction and workability, and meets the needs of rapid prototyping. Its initial setting time can be as short as 34 minutes, and the compressive strength is as high as 9.33 MPa after 7 days; while it can be seen from comparative examples 1 to 5 that directly adding biochar without ball milling cannot achieve the effect of improving the early strength of the barrier control material, and its initial setting time and compressive strength are far worse than those of the biochar-based alkali-activated barrier control material of the present invention. It can be seen from Examples 1-4 and Comparative Example 6 that single ball milling can slightly increase the excitation effect of magnesium oxide, and increases the early strength relative to unmilled magnesium oxide, but this increase is not as obvious as the effect improved by co-ball milling of magnesium oxide and biochar. Comparative Example 8 provides a traditional NaOH-activated slag resistance control material. While ensuring the same pH and mortar-sand ratio as the present invention, the traditional resistance control material has worse workability and fluidity, and is relatively difficult to construct. At the same time, it is limited by lower pH and low mortar-sand ratio, and the traditional resistance control material has strict requirements on alkali equivalent, and the strength development is relatively slow compared to the resistance control material after ball milling.
[0082] The materials prepared in the above embodiments and comparative examples 1 to 8 were tested for resistance control ability:
[0083] The test site is a chemical pollution site in Jiangsu, covering an area of 700m 2 The average content of heavy metal lead in the site is 7000mg / kg, which is 7.75 times higher than the screening value (800mg / kg) for Class II construction land in the "Soil Environmental Quality Construction Land Soil Pollution Risk Control Standard" (GB 36600-2018). The rapid prototyping of biochar-based alkali-induced barrier control materials mentioned in the example was carried out in the range of 5×5m in the chemical pollution site. The specific construction steps include the following:
[0084] (1) Excavate the trench at the proposed barrier location using a trenching machine;
[0085] (2) Prepare gray material and composite alkali activator according to mass percentage, put them into a concrete mixer and mix them evenly for 5 minutes to obtain a premix. Take 60% of the premix and put it into a concrete mixer. Add water to the dry mix according to a water-to-solid mass ratio of 24%, stir at a low speed for 5 minutes to form a muddy slurry, then add the in-situ soil excavated from the excavation tank, stir quickly for 3 minutes, and finally add the remaining 30-40% of the premix, stir quickly for 2 minutes, mix thoroughly to form mud, and pump the mud back to the tank;
[0086] (3) After pouring, cover the top of the barrier material with a layer of in-situ soil to prevent the top from shrinking and cracking and to ensure smoothness.
[0087] Another 5×5m range was selected for comparative example to obtain barrier control materials to compare their permeability performance differences.
[0088] After construction, samples within the range were taken for flexible wall penetration test. The test standard refers to ASTM D5084. The sample was in Pb 2+ The permeability performance under the action of the polluted soil was compared with the permeability coefficient change of the uncontaminated in-situ soil to compare the chemical compatibility. The results are shown in Table 3
[0089] Table 3. Barrier control materials: uncontaminated soil and 7000 mg / kg Pb 2+ Flexible wall penetration by contaminated soil
[0090]
[0091] As shown in Table 3, the permeability coefficient of the uncontaminated soil of each barrier control material in the embodiment is about 1 order of magnitude lower than that of the comparative example, and the permeability coefficient of the embodiment under the action of the contaminated liquid is nearly 5-7 times lower than that of the comparative example; at the same time, according to the requirements of the "Technical Specifications for Vertical Barriers of Industrial Contaminated Sites" (HG / T 20715-2020), the permeability coefficient of the barrier material under the action of tap water must be less than 10 -9 m / s, the permeability coefficient should be less than 10 under the action of pollutants -8 m / s. It can be seen that the comparative example cannot meet the specification requirements, while the experimental examples can meet the specification requirements. This may be because the fine particles caused by ball milling increase the contact reaction area and make the reaction more thorough; the introduction of biochar fills the large pores, making the material more compact and having a good anti-seepage effect.
[0092] The reduction in permeability coefficient in the flexible wall penetration test and the better chemical compatibility under the action of polluted liquid indicate that the barrier control material proposed in the present invention has improved anti-seepage performance compared to traditional barrier control materials. In terms of chemical compatibility, the chemical compatibility of each barrier control material in the embodiment is less than 11, while the chemical compatibility of the comparative example is above 40. In comparison, the traditional cement wall has the worst anti-seepage effect and chemical compatibility. The chemical compatibility of the rapid-forming biochar-based alkali-activated barrier control material proposed in the present invention is significantly better than that of the comparative example. The smaller the chemical compatibility, the more significantly it reduces the spread of pollution, the better the anti-seepage performance, and the stronger the ability to adapt to the environment.
[0093] In Examples 1 to 4, the effects brought about by different biochar contents are different. In order to ensure both rapid molding and excellent anti-seepage performance, the best effect is achieved when the mass ratio of biochar to magnesium oxide is 2:100. The biochar content should not be too high. Although a high biochar content can slightly improve the barrier to pollutants, it will slow down the molding speed, reduce the strength, and make it difficult to retain under the scouring of water.
[0094] The materials obtained in the above embodiments and comparative examples 6-8 were tested for resistance control ability:
[0095] The test site is a coking plant in northern Anhui. The site is polluted by volatile organic compounds such as 1,2-dichloroethane and benzene. Among them, 1,2-dichloroethane is the most serious, with the highest pollution of 102 mg / kg, which is 11.33 times the screening value (9 mg / kg) of Class II construction land in the "Soil Environmental Quality Construction Land Soil Pollution Risk Control Standard" (GB 36600-2018). The rapid prototyping biochar-based alkali-excited barrier control material mentioned in Examples 1-4 is used in this site. The specific construction includes the following steps:
[0096] (1) Excavate the trench at the proposed barrier location using a trenching machine;
[0097] (2) preparing gray material and composite alkali activator according to mass percentage, putting them into a concrete mixer and mixing them evenly for 5 minutes to obtain a premix; taking 60% of the premix and putting it into the concrete mixer, adding water to the dry mix according to a water-solid mass ratio of 24%, stirring at a low speed for 5 minutes to form a muddy slurry, and then adding the in-situ soil excavated from the excavation of the tank body, stirring rapidly for 3 minutes, and finally adding the remaining 30-40% of the premix, stirring rapidly for 2 minutes, fully mixing to form mud, and pumping the mud back to the tank body;
[0098] (3) After pouring, cover the top of the barrier material with a layer of uncontaminated soil to prevent the top from shrinking and cracking and to ensure smoothness.
[0099] At the same time, the barrier control materials mentioned in Examples 6-8 were carried out to compare the barrier properties.
[0100] Since the soil was leveled, the concentration of 1,2-dichloroethane in the soil above the barrier material was tested at regular intervals, and the barrier effect was evaluated based on the change trend. The test results are shown in Table 5.
[0101] Table 4. Barrier performance test results (measured in 1,2-dichloroethane concentration, mg / kg)
[0102] Time / min 0 15 30 60 90 120 150 180 Example 1 MgO@1BC 0 5.82 6.68 8.32 9.54 9.98 10.10 10.12 Example 2 MgO@2BC 0 5.56 6.41 7.95 9.31 9.48 9.60 9.66 Example 3 MgO@3BC 0 5.40 6.01 7.91 8.22 8.39 8.51 8.53 Example 4 MgO@4BC 0 4.92 5.99 7.57 7.74 7.95 8.00 8.02 Comparative Example 6 MgO* 0 10.11 16.75 19.26 22.68 24.55 25.31 26.58 Comparative Example 7 cement 0 8.59 12.76 17.25 20.77 22.41 25.15 25.98 Comparative Example 8 NaOH 0 9.08 12.14 16.01 17.66 19.10 20.04 20.99
[0103] From Table 4 and Figure 4 As shown, the rapid-forming biochar-based alkali-activated barrier control material proposed in the present invention can achieve barrier in about 150 minutes, and compared with traditional alkali-activated barrier materials and cement barrier wall materials, the alkaline ball milling environment provided by magnesium oxide promotes the modification of biochar, and the pores are richer. The adsorption and interception of pollutants can make the seepage concentration of pollutants lower, and the barrier effect is better, which can meet the needs of rapid prototyping. Although traditional materials can also achieve barrier, because they are basically used in long-term maintenance and development situations, they are subject to time, pH and mortar-sand ratio restrictions, and the barrier seepage concentration is relatively high, and the pollution concentration is still increasing during the detection time.
[0104] Therefore, the rapid-forming biochar-based alkali-activated barrier control material of the present invention has better early compressive strength than the untreated magnesium oxide-activated cementitious material under low mortar-sand ratio, and the 7d compressive strength can reach 9.33MPa; at the same time, the presence of biochar and slag can better adsorb and intercept soil pollutants, and has better anti-seepage performance, and the permeability coefficient can reach 2.4×10 -10 m / s. It is relatively quick to block when applied, and the concentration of pollutants seeping out is lower. Compared with cement barrier walls, the production process is low-cost, fast to form, and has low carbon emissions, making it a low-carbon green material.
Claims
1. A biochar-based alkali-activated barrier control material, characterized in that: The biochar-based alkali-activated barrier control material is composed of 50-70% in-situ soil and 30-50% colloidal material by mass; wherein the colloidal material is composed of 90-80% ash material and 10-20% composite alkali activator by mass, and the composite alkali activator is obtained by co-ball milling of activated magnesium oxide and biochar, and the mass ratio of biochar to activated magnesium oxide is 0.5-6:100; the water-solid mass ratio is 22-28%; the preparation method of the composite alkali activator is specifically as follows: screening biochar raw materials and crushing them, pyrolyzing them at 500-700°C for 1-3h to obtain biochar and grinding and sieving them; drying the activated magnesium oxide and biochar at 60-70°C for 4-6h to obtain a dry mixture; The dry mixture is ground in a ball mill for 2-3 hours to obtain a composite alkali activator.
2. The biochar-based alkali-activated barrier control material according to claim 1, characterized in that: The ash material is one or more combinations of blast furnace slag, fly ash, coal gangue, and steel slag.
3. The biochar-based alkali-stimulated barrier control material according to claim 1, characterized in that: In the preparation method of the composite alkali activator, the rotation speed of the ball mill is 100-300 r / min, and the ball-to-material ratio is 4:1-8:
1.
4. The biochar-based alkali-stimulated barrier control material according to claim 1, characterized in that: The magnesium oxide activity is 55-70%, and the biochar particle size is ≤50 μm.
5. A method for preparing the biochar-based alkali-activated barrier control material according to claim 1, characterized in that: The following steps are involved: (1) Prepare ash material and composite alkali activator according to mass percentage, stir and mix evenly for 3-5 minutes to obtain a premix; (2) Take 60-70% of the premix prepared in step (1), add water to the premix at a water-to-solid mass ratio of 22-28%, stir at a low speed for 4-5 minutes to form a muddy slurry, then add in-situ soil at a ratio of 3:7-5:5 of clay and clay, stir rapidly for 2-3 minutes, and finally add the remaining premix and stir rapidly for 2-3 minutes to obtain a biochar-based alkali-activated barrier control material.
6. The method according to claim 5, characterized in that: The curing conditions of the preparation method are 25±2°C and humidity ≥75%.
7. The method according to claim 5, characterized in that: In step (2), the low-speed stirring has a rotation speed of 700-900 r / min; the rapid stirring has a rotation speed of 1500-1800 r / min.
8. An application of the biochar-based alkali-activated barrier control material according to claim 1 in rapid barrier control of emergency contaminated sites and soil pollution control or remediation.
9. The use according to claim 8, characterized in that: The application includes the following steps: excavating a trench at the proposed barrier location by using a trenching machine; configuring a biochar-based alkali-activated barrier control material, and after sufficient mixing, pumping the mud made from the biochar-based alkali-activated barrier control material back into the trench; after pouring, covering the top of the barrier control material with a layer of in-situ soil.
Citation Information
Patent Citations
Anti-cracking low-heat-transfer enhanced vertical blocking barrier material as well as preparation method and application thereof
CN112374807A